Artificial Intelligence based CHATBOT for PMIST websites - et. al., S.Suseela, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A chatbot is used as an agent to communicate with an individual. This may be text-based, or an communicated dialog (within the occasion of voice-based request).Talk bots are fundamentally utilized for data obtaining. It can run on the neighborhood PCs and cell phones, however more often than not it is gotten through the web. Our main aim of this task is to break down client's questions and comprehend client's messages, to give a response to the query of the client exceptionally compellingly, to save the hour of the client since she/he doesn't need to actually go to the institution for request. This framework will assist the understudy with being refreshed about the school exercises. The framework will answer utilizing a compelling GUI which infers that as though a genuine individual is conversing with the client. PMISTBOT is an astute framework created utilizing man-made brainpower (AI) and regular language handling (NLP) calculations. It has a compelling UI and it helps to answer the questions identified with assessment cell, confirmation, scholastics, client's participation and grade point normal, arrangement cell and other different exercises.